The Phenomenon of Social Support: How Does Learning Motivation Relate to Junior High School Students? - Christy, Zefanya Amarya; Soetjiningsih, Christiana Hari (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
This study aims to determine the relationship between peer social support and learning motivation in junior high school. This research method uses a quantitative approach and the sampling technique used is non-probability sampling with a saturated sample. Data collection in this study involved 153 grade VIII students of SMP Negeri 1 Katingan Hilir. Data collection used the Academic Motivation Scale (AMS) scale developed by Deci and Ryan and the social support scale using the social provisions scale developed by Russell and Cutrona which was distributed through the help of google forms. The data analysis technique used is Spearman rank. The results of the data analysis showed that the correlation coefficient was 0.537 with the sig value. 0.000 (p<0.05). These results show that there is a positive and significant relationship between peer social support and learning motivation. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial teman sebaya dengan motivasi belajar pada siswa SMP. Metode penelitian ini menggunakan pendekatan kuantitatif dan teknik sampling yang digunakan yaitu, nonprobability sampling dengan sampel jenuh. Pengambilan data pada penelitian ini melibatkan 153 siswa kelas VIII SMP Negeri 1 Katingan Hilir. Pengumpulan data menggunakan skala Academic Motivation Scale (AMS) yang dikembangkan oleh Deci dan Ryan serta skala dukungan sosial menggunakan social provisions scale yang dikembangkan oleh Russell dan Cutrona yang disebarkan melalui bantuan google form. Teknik analisis data yang digunakan adalah rank spearman. Hasil analisis data menunjukkan bahwa koefisien korelasi sebesar 0,537 dengan nilai sig. 0,000 (p<0,05). Hasil tersebut menunjukkan bahwa adanya hubungan yang positif dan signifikan antara dukungan sosial teman sebaya dengan motivasi belajar.